The analysis and assessment of the enterprises of the production sphere in the course of investment design (Journal of Economic Research & Business Administration, 2015)
The paper has considered theoretical and practical aspects of a technique of the analysis and an assessment of investment risks of the enterprises of the production sphere, in particular, the main features and tasks, receptions of application of a technique in practice are considered. Organizational easures for prevention and neutralization of risks of investments are described.
Keywords: investments; investment project; investment ris; uncertainty; likelihood method; expert method.